Pembelajaran Tematik Holistic Integral di Madrasah Ibtidaiyah - Maria Ulva (Prodi Pendidikan Agama Islam IAI Al-Qodiri Jember, 2022)
Abstract : Integrative thematic learning is a learning approach that integrates various basic competencies from various subjects into various themes. Integrative thematic learning as an effort to integrate the subject or sub-topic between fields of study. This form of integrative learning makes students active, because the teacher only provides a stimulus in the learning process and must be responded to by students. The process of this thematic model is the task of the teacher to provide learning materials in accordance with the direct experiences experienced by students in their lives. So that it makes a process as the core activity of the implementation of learning and the formation of competencies. The method used in this research is qualitative with descriptive research type. In collecting data using interview techniques, observation and documentation. While the data analysis process using Miles and Huberman. The result of this research is holistic integral thematic learning for grade 2 students at MI Unggulan Nuris. These are Thematic subjects that are integrated with religious values. This activity is better known as Project Based Learning. In the implementation of this integral holistic thematic learning, several obstacles were found, namely in its implementation there were no steps or guidebooks in fully integrating the themes carried out by the teacher which had not been well conceptualized. Keywords: Thematic Learning, Holistic Integral